Avaliação do transporte de cargas na cidade de Fortaleza sob o enfoque da logística urbana: diagnóstico e proposição de intervenções - Prata, Bruno de Athayde (2015)
Freight transportation is vital to urban economic development, allowing delivery both of raw material and goods to urban economic players, notwithstanding the negative effects of those flows on the cities such as the impacts on the environment and on the quality of the transport system. Fortaleza, one of the main large Brazilian cities, has presented many problems due to nonexistent policies related to urban freight management. The present work aims to focus the freight transportation problem in Fortaleza, using the concepts of the recently developed area of City Logistics. Data was gathered to make the characterization of present freight transport system problems in the city. As conclusion, the work points out the variables linked with the freight sector that reduce the efficiency of distribution system in Fortaleza city and it shows propositions of urban interventions to face the identified problems.